Friedman’s instrumentalism in F53. A Weberian reading - Peter Galbács (Editura ASE Bucuresti, 2019)
In this paper, Weber’s methodology of ideal types is applied as a framework to argue for the instrumentalist interpretation of Friedman’s methodology of positive economics. Weber’s ideal-typical methodology is characterized as a mix of descriptive inaccuracy and causal adequacy. Based on some recent structuralist results in the philosophy of science it is highlighted how intimately causal understanding and the properties of entities are related. The main contrast between Weber and Friedman consists in the emphases they placed on the causal properties of agents. It is argued that Friedman’s instrumentalism results from his neglect of entity properties for no causal understanding can be placed upon neglected characteristics. By identifying some channels through which methodological Weberianism could spread, the possibility of a real albeit indirect connection between Weber and Friedman is suggested, with Frank H. Knight as the most probable diffuser.